The Role of the Kebumen Regency Local Government in Efforts to Control Shrimp Pond Business in the South Coastal Area of Kebumen Regency - Siti Nur Yuliana (Faculty of Law Universitas Muhammadiyah Purwokerto, 2020)
Kebumen district government encourages the cultivation of shrimp ponds on the south coast. However, in cultivation, it should comply with existing regulations, among others according to the mandate of Law Number 27 of 2009 which was revised to Law Number 1 of 2014 concerning Management of Coastal Areas and Small Islands. In addition, it must be in accordance with the Regional Spatial Plan (RTRW) Number 23 of 2012. The law states that a 100 meter long coastal border is used as a conservation area. So that related to the making of ponds in coastal areas, it should be outside the conservation area. Of course, these rules must be binding. This area is used as a green belt. So that the uneven location must be used according to its designation. In the RTRW it has even been stated that the southern coast, better known as Urut Sewu, is a defense and security area. Especially in the Dislitbang environment of the TNI AD, Setrojenar Village, Buluspesantren District to Mirit District. The proliferation of shrimp ponds in the Urut Sewu area without a permit should be of particular concern to the Kebumen district government. Therefore, this study aims to determine how the role of the regional government of Kebumen Regency in controlling the shrimp pond business in order to comply with the applicable regulations and to know the legal consequences for shrimp farmers who set up a pond business without having a business license. In this study, researchers chose to use descriptive qualitative research methods. Descriptive research aims to provide an overview of a particular symptom. Data collection was carried out by interviewing the Kebumen Licensing Office, the Fisheries and Marine Office of Kebumen Regency, and residents of Jogosimo Village as a sample of shrimp farmers. The results of the research related to the existence of these ponds, related parties provided guidance to the pond owners. As has been done by Satpol PP, the Integrated Investment and Licensing Agency of Kebumen Regency, and the Marine and Fisheries Office of Kebumen Regency. In fact, it was followed up by checking directly into the field. Head of Planning at the Office of Marine Affairs and Fisheries, Kebumen Regency. The government should not only make preventive efforts but also repressive efforts, for example by issuing a special regulation regarding shrimp farming, considering that currently, shrimp ponds are a new livelihood for residents around the southern coast of Kebumen Regency.Keywords: Local Government, Shrimp Farming, Business License